E-Learning, COVID-19, the challenges and way forward - Nurul Shahida, Mohd Shalahim (Kolej Kejuruteraan, 2020)
The COVID-19 pandemic has shifted many existing practices into new compelling norms, where other universities also shared the same experience. The education sector is forced to shift their teaching to e-learning and blended modes. Even before COVID-19, these style of teachings have been adopted, but not well adapted by many academics. With the pandemic not showing any slowdown, academics and students have to adapt to this rapid change. This has generated several challenges and opportunities for both parties, academics and students.